THE EFFECT OF COMPENSATION SATISFACTION, WORKLOAD, AND HOMETOWN ATTACHMENT ON ORGANIZATIONAL COMMITMENT IN PRIVATE SCHOOLS OF ORGANIZATION Y - Jeremia Christian Alexander; Praptini Yulianti (SEAN Institute, 2023)
Education is an important sector for the development of a country. Various phenomena in Indonesian education are related to the amount of compensation, workload, and the number of teachers who migrate. These issues have resulted in many teachers reconsidering their decision to become teachers. Many of these teachers are creative and hardworking teachers and it is unfortunate to see them leave their profession. The objective of this research is to see the effect of compensation satisfaction, workload, and hometown attachment on organizational commitment. This study used a quantitative method where the researcher distributed questionnaires to 152 teachers at private schools of Organization Y in Indonesia and then the data was analyzed using regression. The findings show that compensation satisfaction positively affects organizational commitment, while workload and hometown attachment negatively affect organizational commitment.